The Influence of Obesity on Perioperative Course in High-Risk Patients with Coronary Artery Disease in Cardiac Surgery - Gogayeva, Olena (Ukrainian Journal of Cardiovascular Surgery, 2021)
The aim. To analyze the influence of obesity on the perioperative course in high-risk patients with coronary artery disease (CAD) in cardiac surgery. Material and methods. Retrospective analysis of 354 randomly selected high-risk patients with CAD (ES II > 5%) who underwent surgical intervention and were discharged from the Institute in the period from 2009 to 2019. All the patients underwent routine clinical tests, ECG, echocardiography, coronary angiography and surgical revascularization of the myocardium with correction of concomitant cardiac pathology. Among the patients of the experimental group, 194 (54.8%) had CAD, 132 (37.2%) had postinfarction left ventricular aneurysm, 12 (3.3%) suffered from ischemic mitral regurgitation, 16 (4.5%) patients had CAD and aortic valve disease. Results. Among high-risk patients with CAD, 287 (81.07%) had BMI > 25 kg/m2. Carbohydrate metabolism disorders were found in 208 (72.4%) overweight patients. Type 2 diabetes mellitus (DM) was diagnosed in 78 (27.1%) patients, glucose intolerance was found in 130 (45.2%) cases. Risk stratification according to the ES II scale showed maximum risk (9.8%) in patients with normal body weight and the lowest risk (5.23%) in those with grade III obesity: however, the scale does not take into account anthropometric data. With the increase in body weight, the average number of grafts decreased (3.1 at a BMI of 25-35 kg/m2, 2.6 at a BMI > 40 kg/m2) and the use of internal thoracic arteries increased: 53.7% in patients with normal weight, 66.6% in those with grade III obesity. The level of blood transfusions was the highest (55.2%) in patients with normal weight, and in those with grade III obesity no blood transfusions were performed. Postoperative atrial fibrillation occurred in 14 (20.8%) patients with BMI up to 25 kg/m2, in 30 (28.03%) with BMI 30-29.9 kg/m2 and in 8 (34.7%) patients with grade II obesity. Regardless of body weight, there was a trend towards increase in glucose levels on the first postoperative day with subnormalization until discharge. Acute kidney injury was detected in 3 (4.4%) patients with normal weight, 3 (1.94%) overweight patients, 3 (2.8%) patients with grade I obesity and 1 (33.3%) patient with morbid obesity. Conclusions. Timely preventive measures can help to avoid serious complications even in high-risk patients with obesity. Despite the fact that overweight patients have more severe perioperative period, experience of our Institute allows to operate and treat high-risk patients successfully regardless of their body weight.